On the Social and Empirical Nature of Kant’s Transcendental Anthropocentrism: The Problem of Human Nature - Leszczak, Oleg (Respectus Philologicus, 2019)
This paper presents a conceptual-discursive analysis of Immanuel Kant’s texts from the viewpoint of the ontological essence of humanity (the so-called human nature). On the basis of a functional-pragmatic methodology, the author proposes a metalanguage for a pragmatic conceptual analysis of Kant’s philosophical discourse, together with his own idea of a human as a person, human being, individual, character, and bearer of human traits. The paper consists of two parts. Part One presents the principles by which the human personality is structured, as well as the fundamental methodological questions of the essence of humanity. Part Two analyzes Kant’s notion of “human nature” in both the formal aspect and that of systematic localization. It also considers the issues of social pragmatics and the empirical motivation of “human nature,” which arise from a discursive analysis of texts by Kant. The author attempts to demonstrate that Kant was one of the first philosophers to discern the specificity of human nature in social relations of human personality, which he presented neither in a causal-deterministic form (as a spiritual substance handed down from generation to generation) nor an essentialist one (as a timeless transcendental essence), but rather as a function of social experience for a particular human being (both pragmatic-teleological and transcendental-a posteriori).